Small molecule release from starch matrices - Yusnita Hamzah (University of Nottingham, 2012)
Work by Ferry et al. (2004, 2006a and b) at Nottingham indicated that starchy materials may be better thickeners than other hydrocolloids, at equivalent viscosity, due to their superior flavour release characteristics.